The master and Minerva : disputing women in French medieval culture - Solterer, Helen (University of California Press, 1995)
Annotation Can words do damage? For medieval culture, the answer was unambiguously yes. And as Helen Solterer contends, in French medieval culture the representation of women exemplified the use of injurious language. Solterer investigates the debates over women between masters and their disciples. Across a broad range of Old French literature to the early modern Querelle des femmes, she shows how the figure of the female respondent became an instrument for disputing the dominant models of representing women. The female respondent exploited the criterion of injurious language that so preoccupied medieval masters, and she charged master poets ethically and legally with libel. Solterer's work thus illuminates an early, decisive chapter in the history of defamation.
Keywords: French literature -- To 1500 -- History and criticism.; Women -- France -- History -- Middle Ages, 500-1500.; Women and literature -- France -- History.; Quarreling in literature.; Rhetoric, Medieval.; Dialectic.; Law and literature.; France -- History -- Medieval period, 987-1515.; Littérature française -- Jusqu'à 1500 -- Histoire et critique.; Femmes -- France -- Histoire -- 500-1500 (Moyen Âge); Femmes et littérature -- France -- Histoire.; Querelles dans la littérature.; Rhétorique médiévale.; Dialectique.; Droit et littérature.; France -- Histoire -- 987-1515.; dialectic.; LITERARY CRITICISM -- European -- French.; Dialectic; French literature; Law and literature; Quarreling in literature; Rhetoric, Medieval; Women and literature; Women -- Middle Ages; France; To 1515; Criticism, interpretation, etc.; History